2016
DOI: 10.1007/s10120-016-0629-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of esophagogastric cancer patients enrolled in the National Cancer Institute Cancer Therapy Evaluation Program sponsored phase 1 trials

Abstract: Background In phase 1 trials, an important entry criterion is life expectancy predicted to be more than 90 days, which is generally difficult to predict. The Royal Marsden Hospital (RMH) prognostic score that is determined by lactate dehydrogenase level, albumin level, and number of metastatic sites of disease was developed to help project patient outcomes. There have been no systematic analyses to evaluate the utility of the RMH prognostic score for esophagogastric cancer patients. Methods All nonpediatric ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…This study also showed results consistent with that of previous studies validating the RMH score [ 7 10 , 18 ]. As in other studies which have demonstrated the utility of this score in various types of cancers [ 7 , 8 , 18 ], it showed the prognostic score is effective when applied to a population of varied tumour types, and demonstrates broad applications for clinical trials involving all cancers. The RMH model (Model 1) also significantly predicted the 90-day mortality rate.…”
Section: Discussionsupporting
confidence: 59%
“…This study also showed results consistent with that of previous studies validating the RMH score [ 7 10 , 18 ]. As in other studies which have demonstrated the utility of this score in various types of cancers [ 7 , 8 , 18 ], it showed the prognostic score is effective when applied to a population of varied tumour types, and demonstrates broad applications for clinical trials involving all cancers. The RMH model (Model 1) also significantly predicted the 90-day mortality rate.…”
Section: Discussionsupporting
confidence: 59%
“…Nevertheless, Zhou et al conducted a retrospective study on EJA patients who underwent radical surgery to find that it was the higher preoperative lymphocyte-monocyte ratio (LMR), not NLR or PLR, that independently predicts poor OS [35]. There were a few studies focusing on the association between absolute neutrophil (NE), lymphocyte (LY) or platelet (PLT) counts and EJC prognosis [26,34,[36][37][38]. However, only Fuchs et al found that abnormally low blood levels of LY (HR = 1.31, 95% CI: 1.05 -1.63, p = 0.0015) and high levels of NE (HR = 1.52, 95% CI: 1.17 -1.99, p < 0.0001) were both candidates for predicting risk of EJC patients who underwent 4-month, first-line chemotherapy (platinum and/or fluoropyrimidine with or without an anthracycline) [37].…”
Section: Hematologic Parametersmentioning
confidence: 99%